Outcome Prediction Rule for Neonatal Hypoxic-Ischemic Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
A prognostic model for term infants with postasphyxial hypoxic-ischemic encephalopathy (HIE) based on clinical and laboratory predictors available at age 4 hours was developed at Mount Sinai Hospital and Hospital for Sick Children, Toronto, Ontario.